Trail of Story, Traveller's Path : Reflections on Ethnoecology and Landscape. (Athabasca University Press, 2010)
Trail of Story examines the meaning of landscape, drawn from Leslie Main Johnson's rich experience with diverse environments and peoples, including the Gitksan and Witsuwit'en of northwestern British Columbia, the Kaska Dene of the southern Yukon, and the Gwich'in of the Mackenzie Delta. With passion and conviction, Johnson maintains that our response to our environment shapes our culture, determines our lifestyle, defines our identity, and sets the tone for our relationships and economies. With photos, she documents the landscape and contrasts the ecological relationships with land of First Nations peoples to those of non-indigenous scientists. The result is an absorbing study of local knowledge of place and a broad exploration of the meaning of landscape.
Cover -- Contents -- Figures -- Figure 3.1 Gitksan Territory Map -- Figure 3.2 Gitksan Land: Gitwingak From Across the Skeena River -- Figure 3.3 A Traditional Fishing Site on the Skeena River Above the Village of Ansbayawx (Kispiox), Along the Tenas Hill Trail -- Figure 3.4 Block Diagram of An Idealized Gitksan Landscape -- Figure 3.5 Seven Sisters With Hill in Foreground From Sedan Creek -- Figure 3.6 Tax a Lake: Upper Watson Lake With Mt. Sir Robert in the Background -- Figure 3.7 8220;High Banks8221; Are a Type of Feature Named By Both Gitksan and Athapaskan Speakers -- Figure 3.8 Avalanche Track on Seven Sisters Viewed From Coyote Creek Moraine, July 1995 -- Figure 3.9 Skeena River in Flood: Rough Rapids Where the River Flows Over a Bedrock Obstruction, Described By Dinim Gyet As Lax Kelt Aks 8220;Hilly Water8221; -- Figure 3.10 Confluence of Kispiox and Skeena Rivers From Gwin 8216;Oop Fish Camp: Wilnawaadihl Aks 8216;Where the Waters Get to Know Each Other8217; -- Figure 3.11 Detailed River Terms, of Importance to Those Who Navigate on Rivers and Net Fish 39 -- Figure 4.1 Map of Witsuwit8217;En Territory -- Figure 4.2 Bulkley Valley Landscape -- Figure 4.3 Idealized Witsuwit8217;En Landscape, Bulkley Valley Area -- Figure 4.4 Idealized Witsuwit8217;En Landscape, Nadina Area -- Figure 4.5 View Up Peter Alec Creek Toward N235;din8217;A, Nadina Mountain, May 1989 -- Figure 4.6 Marsh Along Peter Alec Creek, May 1988 -- Figure 4.7 Fishing At Moricetown Canyon on Widzin Kwikh, the Bulkley River -- Figure 4.8 Sdic8217;Odinkhlh Bin, Blue Lake, From the Lake Shore -- Figure 4.9 Hagwilget Canyon, Diyik- At Fall Low Water -- Figure 5.1 Location of Traditional Berry Sites in Relation to the Main Twentieth Century Gitksan and Witsuwit8217;En Villages -- Figure 5.2 Seasonal Round of the Gitksan and Witsuwit8217;En -- Figure 5.3 A Portion of Dinim Gyet8217;s Territory Showing Resource Sites -- Figure 5.4 Map of Shandilla Area -- Figure 5.5A Comparison of Ca. 1899 and 2001 Photos of Shandilla Area From Gitwingak: View of Shandilla Area, Circa 1899 -- Figure 5.5B View of Shandilla Area, 2001 -- Figure 6.1 Generalized Map of Kaska Territory -- Figure 6.2 Liard Canyon Between Watson Lake and Lower Post -- Figure 6.3 Lookout: Old Trail With Blazes -- Figure 6.4 Lookout: Hunting Camp -- Figure 6.5 Lookout: Lake With Fringing Swamp Meadow T Tsel -- Figure 6.6 8220;Rock Mountain8221; Ts Dz233;h -- Figure 6.7 8220;Grass Mountain8221; (Grass-Topped Mountain) H233;s -- Figure 6.8 High Bank Tl8217;233;t G Along the Dease River By the Confluence of French River -- Figure 7.1 Map of Gwich8217;In Settlement Region in the Mackenzie and Peel River Drainages -- Figure 7.2 View of Peel River and Low Arctic Landscape Looking Downstream From Shiltee Rock (Sh236;ldii) -- Figure 7.3 Cluster of Sites in the Road River Area (Northern Yukon) Along Several Intersecting Travel Paths: the River, Trapline Trails, and Portage Trail Along Three Cabin Creek -- Figure 7.4 James Creek Area in the Richardson Mountains, July 2000 -- Figure 7.5 The Summer Fish Camp and Winter Trapping Camp At Road River July 1999 -- Figure 7.6 The Winter Trapping Camp At Road River, February 2000 -- Figure 7.7 Overflow on River Ice, a Challenge of Winter Travel -- Figure 7.8 West Wind With Typical Lenticular Clouds At Road River, February 2000 -- Figure 8.1 Willi.
Includes bibliographical references and index.
Text chiefly in English. Includes text in Gitskan, Gwich'in, Kaska Dene and Witsuwit'en.
Keywords: Landscape ecology -- Canada, Northern; Traditional ecological knowledge -- Canada, Northern; Indians of North America -- Ethnobiology -- Canada, Northern; Landscapes -- Canada, Northern; Names, Geographical -- Canada, Northern; Écologie du paysage -- Canada (Nord); Savoirs écologiques traditionnels -- Canada (Nord); Indiens d'Amérique -- Ethnobiologie -- Canada (Nord); Paysages -- Canada (Nord); Noms géographiques -- Canada (Nord); Landscape ecology; Landscapes; Names, Geographical; Traditional ecological knowledge; Northern Canada; Electronic resource